-(-30)-(-x)=13
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
13 x 3 - 2 = 13 : S
180 + 30 : 6 = 35 : S
30 + 60 x 2 = 180 : S
282 - 100 : 2 = 232 : Đ
\(\dfrac{7}{16}+\dfrac{-1}{8}+\dfrac{9}{32}=\dfrac{14}{32}-\dfrac{4}{32}+\dfrac{9}{32}=\dfrac{19}{32}\)
\(\dfrac{5}{4}-\dfrac{25}{30}\times\dfrac{37}{44}+\dfrac{-25}{30}\times\dfrac{13}{44}+\dfrac{-25}{30}\times\dfrac{-6}{44}\)
\(=-\dfrac{25}{30}\times\left(\dfrac{5}{4}+\dfrac{37}{44}+\dfrac{13}{44}-\dfrac{6}{44}\right)\)
\(=-\dfrac{25}{30}\times\left(\dfrac{55}{44}+\dfrac{37}{44}+\dfrac{13}{44}-\dfrac{6}{44}\right)\)
\(=-\dfrac{25}{30}\times\dfrac{99}{44}\)
\(=-\dfrac{5}{6}\times\dfrac{9}{4}\)
\(=-\dfrac{15}{8}\)
\(\left(\dfrac{7}{16}+\dfrac{-1}{8}+\dfrac{9}{32}\right):\dfrac{5}{4}\)
\(=\left(\dfrac{14}{32}+\dfrac{-4}{32}+\dfrac{9}{32}\right):\dfrac{5}{4}\)
\(=\dfrac{19}{32}:\dfrac{5}{4}\)
\(=\dfrac{19}{32}.\dfrac{4}{5}=\dfrac{19.4}{32.5}=\dfrac{19}{40}\)
\(\dfrac{-25}{30}.\dfrac{37}{44}+\dfrac{-25}{30}.\dfrac{13}{44}+\dfrac{-25}{30}.\dfrac{-6}{44}\)
\(=\dfrac{-25}{30}.\left(\dfrac{37}{44}+\dfrac{13}{44}+\dfrac{-6}{44}\right)\)
\(=\dfrac{-25}{30}.\dfrac{44}{44}=\dfrac{-5}{6}.1=-\dfrac{5}{6}\)
a) Ta có: (-30)-(-x)=13
\(\Leftrightarrow-30+x=13\)
\(\Leftrightarrow x-30=13\)
\(\Leftrightarrow x=13+30=43\)
Vậy: x=43
a: =1/6+17/6-4/13+30/13
=3+2
=5
b: =28,8:3,25*2,5
=72:3,25
=288/13
-(-30)-(-x)=30
30+x=30
x=30-30
x=0
vậy x=0
-(-30)-(-x)=13
30+x=13
=> x= 13 - 30
x= -17